New political order in the DR Congo? the transformation of regulation - Vlassenroot, Koen; Raeymaekers, Timothy (Afrika Focus, 2008)
It has been said repeatedly: the Democratic Republic of Congo (formerly Zaire) remains only a shadow of its former self, a typical case of state failure and collapse. Closer observation suggests a different image, however: not only has this country demonstrated “a remarkable propensity for resilience” (Englebert, 2003), its administration and regulatory frameworks – which in some domains have not changed since colonial times – have remained largely intact even during the latest period of war and political turmoil. In this article, we would like to explain these different “cross currents and contradictions” (Young, 2004) that emerged during the past Congolese war, addressing the question of whether processes of state erosion and political reconfiguration during this period should be described as a further “privatisation of the state”, as proposed by Hibou and others, or rather as a transformation or commodification of state sovereignty. The article is organized diachronically: it first discusses the Mobutu period (1965-1997), and then the war (1996-2003), to finally draw some conclusions from Congo’s long period of political “transition”. Key words: Congo, conflict, non-state regulation, Armed groups